Decreased immunosuppressive actions of 1α, 25-dihydroxyvitamin D3 in patients with immune thrombocytopenia. (October 2016) - Liu, Wenjie; Li, Huiyuan; Hao, Yating; Li, Yang; Lv, Mingen; Xue, Feng; Liu, Xiaofan; Zhang, Lei; Yang, Renchi
Highlights: Local 1, 25(OH)2 D3 levels and VDR mRNA were decreased in active ITP patients. 1, 25(OH)2 D3 /VDR had anti-proliferation effect on lymphocytes in ITP patients. 1, 25(OH)2 D3 /VDR reverses the abnormal T cells polarization in ITP. Abstract: Primary immune thrombocytopenia (ITP) is an acquired autoimmune disease. 1α, 25-dihydroxyvitamin D3 [1, 25(OH)2 D3 ] and vitamin D receptor (VDR) play important immune-suppressive roles in immune system. It has been reported that serum 1, 25(OH)2 D3 were lower in ITP patients. In this study, we evaluated local 1, 25(OH)2 D3 level and VDR mRNA expression further, and determined whether 1, 25(OH)2 D3 /VDR were correlated with T cell dysfunction in ITP patients. We found that 1, 25(OH)2 D3 /VDR levels were decreased in active ITP patients, and 1, 25(OH)2 D3 had significant anti-inflammatory effects on ITP patients, including both anti-proliferation of peripheral blood mononuclear cells (PBMCs) and reversing the abnormal T cells polarization. 1, 25(OH)2 D3 inhibited the differentiation of T helper (Th)1 and Tc1 cells but induced the differentiation of Th2, Tc2 and T regulatory (Treg) cells in ITP patients. However, the percentage of Th17 cells were not affected obviously with 1, 25(OH)2 D3 . In addition, 1, 25(OH)2 D3 also suppressed pro-inflammatory cytokines (INF-γ and IL-17A) but promoted anti-inflammatory cytokine (IL-10) secretion in ITP patients. In conclusion, decreased 1, 25(OH)2 D3 /VDR might participate in the pathogenesis of ITP, and appropriate supplement of 1, 25(OH)2 D3 may be a promising treatment.